Two Two Three Three Four Four

Algebra Level 4

The complex roots of :

( x + 2 ) 2 + ( x + 3 ) 3 = ( x + 4 ) 4 (x+2)^{2}+(x+3)^{3}=(x+4)^{4}

are a ± b i c \frac{-a\pm\sqrt{b}i}{c} for positive coprime integers a , b , c a,b,c .

Find a + b + c a+b+c .

Details and Assumptions

i 2 = 1 i^2 = -1


The answer is 20.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
Dec 19, 2014

( x + 2 ) 2 + ( x + 3 ) 3 = ( x + 4 ) 4 (x+2)^2+(x+3)^3 =(x+4)^4

( x 2 + 4 x + 4 ) + ( x 3 + 9 x 2 + 27 x + 27 ) \Rightarrow (x^2 + 4x + 4) + (x^3 + 9x^2 + 27x + 27) = x 4 + 16 x 3 + 96 x 2 + 256 x + 256 \quad \space = x^4 + 16x^3 + 96x^2 + 256x + 256

x 4 + 15 x 3 + 86 x 2 + 225 x + 225 = 0 \Rightarrow x^4 + 15x^3 + 86x^2 + 225x + 225 = 0

( x + 3 ) ( x + 5 ) ( x 2 + 7 x + 15 ) = 0 \Rightarrow (x+3)(x+5)(x^2 + 7x + 15) = 0

x = 3 \Rightarrow x = -3 , x = 5 x=-5 and

x = 7 ± 7 2 4 ( 2 ) ( 15 ) 2 = 7 ± 11 2 = 7 ± 11 i 2 \quad \quad \quad \quad x = \dfrac {-7 \pm \sqrt{7^2-4(2)(15)}}{2} = \dfrac {-7 \pm \sqrt{-11}}{2} = \dfrac {-7 \pm \sqrt{11}i}{2}

a = 7 \Rightarrow a= 7 , b = 11 b=11 and c = 2 a + b + c = 7 + 11 + 2 = 20 c=2\quad \Rightarrow a+b+c = 7+11+2 = \boxed {20}

\text{To simplify calculations, y=x+4 so f(y)= (y-2)^2+(y-1)^3 -y^4}\\f(1)=0, f(-1)=0,\therefore \dfrac{f(y)}{y^2-1}=0\text{ gives function with complex roots.}\\\therefore ~ \dfrac{f(y)}{y^2-1}=y^2-y+3=0.~~\implies~y=\dfrac{1\pm \sqrt{1^2-12}}{2}=\dfrac{1\pm \sqrt{11}i}{2}\\=x+4.~\therefore~a=7,b=11,c=2

Nikola Djuric
Dec 3, 2014

After calculating we get xxxx+15xxx+86xx+225x+225=0,This Polynomial can be written as (xx+7x+15)(xx+8x+15)=0.so complex roots are (-7±i√11)/2 ,so a=7,b=11,c=2 and a+b+c=20

Can you please explain how this is different from that of Chew-Seong Cheong ? Thanks.

Niranjan Khanderia - 6 years, 3 months ago
John Gilling
May 22, 2015

For an even slightly easier calculation, we can set z = x + 3 z=x+3 , so the equation becomes ( z 1 ) 2 + z 3 = ( z + 1 ) 4 . (z-1)^2+z^3=(z+1)^4. Then z=0 and z=-2 are two fairly self-evident real roots, and the variable change gives us x=-3 and x=-5, from which we can use synthetic division to find that the remaining quadratic polynomial is x 2 + 7 x + 15. x^2+7x+15. The solution follows.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...